Discovery of highly specific protein markers for the identification of biological stains. Issue 21 (1st October 2014) - Legg, Kevin M.; Powell, Roger; Reisdorph, Nichole; Reisdorph, Rick; Danielson, Phillip B.; McCord, Bruce
<x xml:space="preserve">Abstract</x> DNA profiling has transformed the field of forensic biology by making it possible to individualize biological stains. The identification of the stain itself, however, continues to present forensic serologists with significant challenges. Current antibody‐ and enzyme activity‐based assays yield only presumptive results as detection in nontarget body fluids or cross‐reactivity with nonhuman sources have both been well documented. For other critical body fluids such as vaginal and menstrual fluids, there are no commercial tests at all. Using a three‐pronged, comparative proteomic strategy based on proteome fractionation by HPLC followed by MS, a panel of 29 candidate protein biomarkers have been proposed as highly specific indicators of human saliva, urine, seminal fluid, vaginal fluid, peripheral blood, and menstrual fluid. The combination of consistent identification by multiple strategies in the current study; confirmation in independently compiled proteomic databases; and information on tissue expression and/or functionality from the proteomic literature all support the proposition that these proteins will have utility as reliable biomarkers of their target body fluids. The identification of candidate high‐specificity protein biomarkers for human body fluids encountered in forensic investigations lays the foundation for the development of faster and more reliable approaches to the serological analysis of evidentiary stains.